2009
DOI: 10.1016/j.cam.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective possibilistic model for portfolio selection with transaction cost

Abstract: a b s t r a c tIn this paper, we introduce the possibilistic mean value and variance of continuous distribution, rather than probability distributions. We propose a multi-objective Portfolio based model and added another entropy objective function to generate a well diversified asset portfolio within optimal asset allocation. For quantifying any potential return and risk, portfolio liquidity is taken into account and a multi-objective non-linear programming model for portfolio rebalancing with transaction cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 12 publications
0
41
0
3
Order By: Relevance
“…Jana et al (2009) showed that this technique can be applied in portfolio optimization problem. Fuzzy programming technique follows these steps for solving the problem that is shown in Eq.…”
Section: Fuzzy Programming Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Jana et al (2009) showed that this technique can be applied in portfolio optimization problem. Fuzzy programming technique follows these steps for solving the problem that is shown in Eq.…”
Section: Fuzzy Programming Techniquementioning
confidence: 99%
“…They solved their model using fuzzy mathematical programming. Jana et al (2009) proposed a possibilistic model with transaction cost and entropy function in objective functions. Chang et al (2009) considered different risk measures in their model such as variance, semivariance, variance with skewness and absolute deviation, and solved it using genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Iš išanalizuotos portfelio optimizavimo literatūros matyti, kad vis dažniau mokslininkai padaro išvadą, kad į investicijų portfelio sudarymo uždavinį prie pelningumo ir rizikos tikslinga įtraukti papildomus parametrus ir kad portfelio optimizavimas turi būti daugiakriterinis (Steuer et al 2007(Steuer et al , 2008. Kaip trečiasis parametras buvo naudojamas likvidumas (Jana et al 2009;Lo et al 2003), asimetrija (Prakash et al 2003;Konno et al 1993;Konno, Yamamoto 2005;Briec et al 2005;Kerstens et al 2008), plotis arba neapibrėžtumas (Smimou et al 2008), sąlyginė rizikuojamoji vertė -CVaR (Aboulaich et al 2010). Kai kuriais atvejais rizikai portfelyje išreikšti naudotas ne klasikinis standartinis nuokrypis, o kiti matai -absoliutus ir semiabsoliutus nuokrypis (Fang et al 2006), rizikuojamoji vertė (VaR) (Soler et al 2010).…”
Section: įVadasunclassified
“…The possibilistic mean, variance and covariance of fuzzy numbers, defined by Carlsson and Fullér 12 , were used to solve many real world problems. For example, Carlsson et al 16 and Jana et al 17 applied possibilistic mean value and variance to solve Markowitz mean-variance portfolio selection problem under the assumption that the returns of assets were fuzzy numbers. Zhang and Xiao 18 applied weighted possibilistic mean and variance of fuzzy numbers to the decision making.…”
Section: Introductionmentioning
confidence: 99%